Penyusunan Laporan Keuangan Sederhana Untuk Pengusaha Kecil (Studi Pada Pengusaha Kecil Di Kecamatan Medan Labuhan) - Ruswan Nurmadi; Liza Novietta (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
At this time, there are still many small entrepreneurs who have not succeeded in compiling a simple financial report. Loans provided by banks to be distributed to small and medium enterprises have not been fully absorbed. One of the main obstacles faced by small and medium enterprises in developing their business is the absence of financial reporting that are required to obtain business loans from banks. On the other hand, for labor absorption, small and medium enterprises contributions are more than 90 percent in Indonesia. This shows how important the role of small and medium enterprises in the Indonesian economy. This research takes data in Medan Labuhan Sub-District, where small and medium enterprises unable to develop their business due to financial constraints.